Design an Automatic Flour Packing System With the Programmable Logic Controller System - Suryo, Sumar H (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2021)
To facilitate marketing so it is necessary to organize the packaging / packaging process. One of the production activities in terms of filling and packaging flour still uses human labour and it takes 2 workers for producing 100 sacks of flour in 3 hours in a 20 kg package. The manual method used by the workers can prove that it takes a long time to process the flour filling and packaging. After observing the problems experienced by workers, therefore the authors took the initiative to create a device that can carry out the filling and packaging process of flour automatically by utilizing a PLC (Programmable Logic Controller) as a controller, proximity optical sensors as packaging detectors in the filling place, load cell sensors. as a detector for the weight of flour to be weighed and the weighing result is displayed on the LCD. Packages that have been filled with 2 kg of flour will be carried by a conveyor for the packing process using a sewing machine. From the test results, it is found that the filling process of flour weighing 2 kg is displayed on the LCD and also the packaging process takes 20 seconds.